2016
DOI: 10.1155/2016/6836080
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects of Pomegranate Peel Extract in THP‐1 Cells Exposed to Particulate Matter PM10

Abstract: Epidemiological and experimental evidence support health risks associated with the exposure to airborne particulate matter with a diameter of <10 μM (PM10). PM10 stimulates the production of reactive oxygen species (ROS) and inflammatory mediators. Thus, we assumed that natural antioxidants might provide health benefits attenuating hazardous effects of PM10. In the present study, we examined the effects of pomegranate peel extract (PPE) on THP-1 monocytic cells exposed to PM10. PM10 induced cytotoxicity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…An extract of Eucheuma cottonii reduces both the accumulation of alveolar macrophages and the serum levels of malondialdehyde in PM10 coal dust-exposed rats, indicating that the extract attenuates inflammation and oxidative stress resulting from chronic coal dust exposure [26]. We previously demonstrated that pomegranate peel extract and punicalagin attenuate PM10-induced ROS production, the expression of TNF-α, IL-1β, monocyte chemoattractant protein-1, and intercellular adhesion molecule-1 in THP-1 human acute monocytic leukemia cells, indicating their anti-inflammatory activities against particulate matter-induced inflammation [20]. However, the efficacy of the plant extracts or their constituents on skin cells exposed to air pollution remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An extract of Eucheuma cottonii reduces both the accumulation of alveolar macrophages and the serum levels of malondialdehyde in PM10 coal dust-exposed rats, indicating that the extract attenuates inflammation and oxidative stress resulting from chronic coal dust exposure [26]. We previously demonstrated that pomegranate peel extract and punicalagin attenuate PM10-induced ROS production, the expression of TNF-α, IL-1β, monocyte chemoattractant protein-1, and intercellular adhesion molecule-1 in THP-1 human acute monocytic leukemia cells, indicating their anti-inflammatory activities against particulate matter-induced inflammation [20]. However, the efficacy of the plant extracts or their constituents on skin cells exposed to air pollution remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that pomegranate peel extract attenuates the oxidative and inflammatory responses of monocytes exposed to PM10 [20]. However, the effects of polyphenols on PM10-exposed skin cells remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pomegranate extracts have broad bioactivities including antimicrobial, antiinflammatory and anti‐tumor effects (Betanzos‐Cabrera et al, ; Ma et al, ; Park et al, ) and have been used in traditional Uyghur medicine for thousands of years. Our results show that GA decreased membrane CYP51 enzyme activity and increased fungal lanosterol in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The extract of Eucheuma cottonii attenuated inflammation and oxidative stress induced by chronic exposure to coal dust in rats [ 10 ]. Pomegranate peel extract and punicalagin attenuated the PM10-induced adhesion of THP-1 cells to endothelial cells, which was indicative of its anti-inflammatory activity against particulate matter [ 11 ].…”
Section: Introductionmentioning
confidence: 99%